2019
DOI: 10.1038/s41566-019-0496-1
|View full text |Cite
|
Sign up to set email alerts
|

Suppressed Auger scattering and tunable light emission of Landau-quantized massless Kane electrons

Abstract: The Landau level laser has been proposed a long time ago as a unique source of monochromatic radiation, widely tunable in the THz and infrared spectral ranges using an externally applied magnetic field. In spite of decades of efforts, this appealing concept never resulted in the design of a reliable device. This is due to efficient Auger scattering of Landau-quantized electrons, which is an intrinsic non-radiative recombination channel that eventually gains over cyclotron emission in all materials studied so f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 37 publications
1
17
0
2
Order By: Relevance
“…The hypothesized carrier dynamics of the strained graphene with pseudo-Landau levels is unambiguously captured in the temporal evolution of −Δ R / R in the slow regime. This slow carrier dynamics in the presence of pseudo-Landau levels can be explained by the significant reduction of phase space for scattering processes, which has also been experimentally observed in pristine graphene 52 and other materials 18 , 53 but only in the presence of an external magnetic field.…”
Section: Resultsmentioning
confidence: 57%
See 1 more Smart Citation
“…The hypothesized carrier dynamics of the strained graphene with pseudo-Landau levels is unambiguously captured in the temporal evolution of −Δ R / R in the slow regime. This slow carrier dynamics in the presence of pseudo-Landau levels can be explained by the significant reduction of phase space for scattering processes, which has also been experimentally observed in pristine graphene 52 and other materials 18 , 53 but only in the presence of an external magnetic field.…”
Section: Resultsmentioning
confidence: 57%
“…Since then, scanning tunneling spectroscopy (STS) measurements have repeatedly confirmed that pseudomagnetic fields in mechanically deformed graphene can reach up to a few hundred T [11][12][13][14][15][16] . These giant pseudo-magnetic fields can form significant energy gaps 7 and substantially modify optical transitions in the same manner as an external magnetic field [17][18][19][20] , but to a previously unattainable extent due to the high strength of pseudo-magnetic fields. However, the influence of pseudomagnetic fields on the optical properties of graphene has not yet been experimentally verified.…”
mentioning
confidence: 99%
“…Исследование же более узкозонных слоев, а также гетероструктур с КЯ на основе КРТ долгое время сдерживалось ограниченными возможностями роста таких структур, и лишь относительно недавно был достигнут значительный прогресс в технологии молекулярно-лучевой эпитаксии (МЛЭ) структур на основе HgCdTe, что возродило интерес к изучению их свойств [5,6]. При этом фокус в исследованиях таких структур сместился в область эффектов, обусловленных законом дисперсии носителей заряда и инверсией зон, в частности, были продемонстрированы возникновение состояния топологического изолятора в двумерных [7] и трехмерных структурах [8], наличие псевдорелятивистских частиц -безмассовых фермионов Дирака в безмассовых КЯ [9] и фермионов Кейна в объемных пленках КРТ [10][11][12]. Структуры на основе КРТ могут оказаться перспективным материалом для создания детекторов и источников излучения дальнего и среднего инфракрасного диапазона, в частности при разработке лазеров на межзонных переходах [13,14] и для приложений в области абсорбционной и гетеродинной спектроскопии с временны ым разрешением в длинноволновой части среднего ИК диапазона (длина волны излучения 9−30 мкм).…”
Section: Introductionunclassified
“…[ 31 ] This interest has been driven by the observation of 3D massless Kane fermions in films with x=xnormalc, [ 32 ] followed by detailed studies using magneto‐ and terahertz‐spectroscopy. [ 33–35 ] Topological insulators (TIs) based on bulk films with Cd contents below the temperature‐dependent critical xnormalc remain less studied so far. [ 36,37 ] These materials, however, have a number of advantages with respect to HgTe TIs.…”
Section: Introductionmentioning
confidence: 99%